Atomic Layer Deposition of Cobalt Phosphide for Efficient Water Splitting. Issue 39 (7th August 2020) - Zhang, Haojie; Hagen, Dirk J.; Li, Xiaopeng; Graff, Andreas; Heyroth, Frank; Fuhrmann, Bodo; Kostanovskiy, Ilya; Schweizer, Stefan L.; Caddeo, Francesco; Maijenburg, A. Wouter; Parkin, Stuart; Wehrspohn, Ralf B.
Abstract: Transition‐metal phosphides (TMP) prepared by atomic layer deposition (ALD) are reported for the first time. Ultrathin Co‐P films were deposited by using PH3 plasma as the phosphorus source and an extra H2 plasma step to remove excess P in the growing films. The optimized ALD process proceeded by self‐limited layer‐by‐layer growth, and the deposited Co‐P films were highly pure and smooth. The Co‐P films deposited via ALD exhibited better electrochemical and photoelectrochemical hydrogen evolution reaction (HER) activities than similar Co‐P films prepared by the traditional post‐phosphorization method. Moreover, the deposition of ultrathin Co‐P films on periodic trenches was demonstrated, which highlights the broad and promising potential application of this ALD process for a conformal coating of TMP films on complex three‐dimensional (3D) architectures. Abstract : Cobalt phosphide is prepared by atomic layer deposition for the first time. The optimized recipe employs an extra H2 plasma step to remove excess phosphorus. The as‐deposited Co‐P films demonstrate significantly higher activities towards electrochemical and photoelectrochemical hydrogen evolution reaction than that prepared by a traditional method.